Politicisation of public administration in France - Berthelot, Clara (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
This paper proposes a model of analysis of the forms of politicization in the public administration on French case. The purpose of this paper is to present politicisation as a dynamic process of changes in public administration.
Keywords: politicisation; France; public administration